Analysis of Segmental Lymph Node Metastasis and Clinical Features in cT1N0M0 Lung Adenocarcinoma. (18th February 2020) - Sun, Guanghao; Sun, Yanbin; Zou, Zifang; Xu, Shun
Abstract : The progression of lung adenocarcinoma through lymph node metastasis has been well established; however, the process of segmental lymph node (LSN) metastasis in cT1N0M0 lung adenocarcinoma remains unclear. We aimed to elucidate the markers of lymph node metastasis to different segments in early-stage lung adenocarcinoma and identify new indications for segmentectomy. A total of 200 patients were enrolled in this study. These patients were diagnosed with cT1N0M0 lung adenocarcinoma after positron emission tomography/computed tomography and received lobectomy and lymph node dissection surgeries. Lymph nodes retrieved from each station were sorted. The metastatic status of the isolated (i) LSNs and several characteristics were analyzed. Patients with ground-glass nodules (GGNs) (P = 0.025 ), AIS/MIA/lepidic adenocarcinoma (P = 0.038 ), nodules with a maximum diameter ≤1 cm (P = 0.017 ), maximum standardized uptake value (SUVmax ) < 2.5 (P = 0.029 ), serum carcinoembryonic antigen (CEA) levels ≤4.5 ng/ml (P = 0.036 ), and no N1 lymph nodes metastasis (P = 0.036 ) had significantly lower iLSN metastasis rates than those without these characteristics. Pure GGNs, CEA levels ≤4.5 ng/ml, SUVmax < 2.5, tumors with a maximum diameter of ≤1 cm, or those confirmed to be adenocarcinoma in situ, minimally invasive adenocarcinoma, or invasive lepidic-predominant adenocarcinoma by frozen section may indicate segmentectomy. However, segmentectomy is not suitable for patients with metastasis to the N1 lymph nodes.